Modelling of lithium-titanate attery with ambient temperature effect for charger design - Low, W. Y. (Institution of Engineering and Technology, 2016)
Lithium-titanate battery is a new generation of lithium-ion battery that offers an outstandingly fast charging capability. Its charging profile forms the basis for an efficient battery charger design for the battery. As a remedial solution, this study proposes a mathematical model to capture the charging profiles of the lithium-titanate battery at different charging rates and ambient temperatures. In this aspect, the charging characteristic of lithium-titanate battery is represented by a transfer function, which is applicable for small-signal analysis and large-signal simulation of battery charger design. The methodology of battery modelling is solely based on the constant-current charging profiles of a battery. Enhanced charging curve normalisation method is applied to obtain the charging characteristic of battery. A novel temperature-based equation is developed to represent the normalised charging curves at different ambient temperatures. Then, a transfer function-based model is developed to simulate the charging profiles of battery. The developed model is validated through experimental studies. Comparison of experimental and simulation results shows that the developed model is able to capture the charging behaviour of a lithium-titanate battery for various charging rates and temperatures.